2009
DOI: 10.1108/01437720910973025
|View full text |Cite
|
Sign up to set email alerts
|

Comparing levels of job satisfaction in the countries of Western and Eastern Europe

Abstract: Against the plethora of studies of the factors influencing job satisfaction, this paper makes three contributions. First, in contrast to most studies of job satisfaction which are country-specific, the scope of this paper extends to 33 different countries. Comparing different countries on the basis of their mean job satisfaction scores ignores inequality in the distribution of scores between the countries' individual respondents: the paper's second contribution is to construct "equity-sensitive" job satisfacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
33
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 37 publications
6
33
0
Order By: Relevance
“…The impact of age also has not been clearly proved in the existing literature. Clark (1996) demonstrated that job satisfaction was U-shaped with age while Borooah (2009) showed that young and middle-aged people were less likely to have a high level of satisfaction than older workers (aged 50 years or above) in both EE and WE.…”
Section: Conceptual Framework and Literature Overviewmentioning
confidence: 96%
See 2 more Smart Citations
“…The impact of age also has not been clearly proved in the existing literature. Clark (1996) demonstrated that job satisfaction was U-shaped with age while Borooah (2009) showed that young and middle-aged people were less likely to have a high level of satisfaction than older workers (aged 50 years or above) in both EE and WE.…”
Section: Conceptual Framework and Literature Overviewmentioning
confidence: 96%
“…Večerník (2004) and Torgler (2011) analysed work values and found substantial differences between WE and EE. Borooah (2009) showed that the average level of job satisfaction was higher in WE than in EE. Similarly, Sousa-Poza and Sousa-Poza (2000b) ranked five EE countries behind WE countries in their research.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…sense of responsibility, social interaction), while workers from transition countries valued more the external aspects (e.g. pay, holidays) [9]. Meanwhile, real wages dropped to 40−90% of 1989 levels across post-communist countries [2].…”
Section: Work Concernsmentioning
confidence: 99%
“…Large-scale privatization was launched later and is still to be completed in the Western Balkans and the Commonwealth of Independent States. While the earlier reforms improved individual perceptions of the transition, and hence SWB, the large-scale privatization process had the opposite effect, in that it solidified the popular view of business and political leadership benefiting from the reforms and, as a result, pushed down the SWB of people [9]. Perceived lawlessness, corruption, bad governance, and low legitimacy of the new institutions are still the characteristics of some transition countries; yet these factors have an unclear impact on SWB in the post-communist region [7], [11].…”
Section: Social and Institutional Concernsmentioning
confidence: 99%